Development and implementation of novel drug delivery system for transdermal materials - Sun, Yu, author; Li, Yan Vivian, advisor; Liu, Jiangguo, advisor; Bailey, Travis, committee member; Gentry-Weeks, Claudia, committee member (Colorado State University. Libraries, 2024)
There is a constant need for developing transdermal dressing materials with advanced properties such as infection monitoring and wound closure facilitation for effective chronic wound treatments. On the other than, the advancement in drug delivery systems has created innovation of precise targeting of treatment, nontoxicity, cell access, controlled release profiles, treatment variations, and antibiotics activity conservation, which offers a great opportunity in developing novel wound dressing materials. Recently, the application of nanomaterials, especially nanoparticles, in drug delivery systems has shown great potential in effective wound treatment. In this proposal, three projects are focused on developing nanostructured scaffolds loaded with antibiotic agents for novel wound dressing applications. First, the antibiotic encapsulated poly (lactic-co-glycolic acid) (PLGA) nanoparticles will be integrated into monolithic nanofiber scaffolds that can be tested in transdermal materials for antibacterial properties. Second, the antibiotics loaded PLGA nanoparticles incorporated monolithic nanofiber scaffolds will be developed into core-shell fibrous scaffolds to provide a drug delivery system with controlled release of antibiotics. Integration of the nanoparticles into nanofibers includes monolithic and core-shell structures to provide controlled release of antibiotic agents. The mechanisms of controlled release are investigated via experimental and computational methods. Finite difference methods and machine learning are used for developing mathematical models capable of numerically quantifying antibiotic release rates, which provides a theoretical understanding of the release process in the nanostructure scaffolds. The work provides implication of utilizing PLGA nanoparticles in scaffolds to develop effective transdermal materials. Additionally, the computational models would provide tools to understand the mechanism of controlled release process, which may assist in the design of the nanoparticles as well as the nanostructured scaffolds.
Keywords: core-shell fibrous scaffolds; machine learning; transdermal materials; drug delivery systems; coaxial-electrospinning; PLGA nanoparticle